Vegetacijska raziskovanja in kartiranje v Sloveniji - Zupančič, Mitja (Zbornik gozdarstva in lesarstva, 2003)
The temporal development of research and above all mapping of vegetation in Slovenia in the period from the end of the 1920s to the 1990s is presented. Most of the vegetation research and mapping was carried out between the 1950s and 1980s, especially in the sphere of forest vegetation.
Keywords: fitocenologija; kartiranje; Slovenija; vegetacija; vegetacijske karte; zgodovinski pregledi